Targeting Breast Cancer and Their Stem Cell Population through AMPK Activation: Novel Insights - Bhawna Uprety; Heidi Abrahamse (Cells, 2022)
Despite some significant advancements, breast cancer has become the most prevalent cancer in the world. One of the main reasons for failure in treatment and metastasis has been attributed to the presence of cancer initiating cells—cancer stem cells. Consequently, research is now being focussed on targeting cancer cells along with their stem cell population. Non-oncology drugs are gaining increasing attention for their potent anticancer activities. Metformin, a drug commonly used to treat type 2 diabetes, is the best example in this regard. It exerts its therapeutic action by activating 5′ adenosine monophosphate-activated protein kinase (AMPK). Activated AMPK subsequently phosphorylates and targets several cellular pathways involved in cell growth and proliferation and the maintenance of stem-like properties of cancer stem cells. Therefore, AMPK is emerging as a target of choice for developing effective anticancer drugs. Vanadium compounds are well-known PTP inhibitors and AMPK activators. They find extensive applications in treatment of diabetes and obesity via PTP1B inhibition and AMPK-mediated inhibition of adipogenesis. However, their role in targeting cancer stem cells has not been explored yet. This review is an attempt to establish the applications of insulin mimetic vanadium compounds for the treatment of breast cancer by AMPK activation and PTP1B inhibition pathways.